Exploratory Evaluation of Retranslocation and Bioconcentration of Heavy Metals in Three Species of Mangrove at Las Cucharillas Marsh, Puerto Rico - MejÃas, Carla Lorraine; Musa, Juan Carlos; Otero, Juan (Journal of Tropical Life Science, 2013)
Heavy metal contamination in the coastal area of CataÃ±o, Puerto Rico accountable to anthropogenic sources is of great concern due to the risk posed over the surrounding communities and adjacent ecosystems. Estuarine ecosystems are widely recognized for the presence of mangroves. This type of flora is recognized for their many beneficial properties for example, the ability to purge aquatic ecosystems where they stand. Exploratory analyses on the phytoaccumulative capacity of three mangrove species for ten metals (Hg, Al, As, Cd, Cr, Cu, Fe, Pb, Mg, Zn) were performed in this research. Random soil samples and both green and senescent leaves of Rhizophora mangle, Laguncularia racemosa and Avicennia germinans from three different sites of Peninsula La Esperanza were analyzed in order to apply the retranslocation efficiency (RT%) and bioconcentration factor (BCF) concepts. After calculating the RT% and the BCF, comparison analyses among the three mangrove species were performed. In general, the results showed low RT% values for Avicennia in comparison with Rhizophora and Laguncularia. BCF values confirmed RT% results for Avicennia, showing higher heavy metal concentrations in its senescent leaves in contrast with the other species. Therefore, these preliminary results suggest that Rhizophora and Laguncularia act better as phytoremediators for heavy metals in polluted areas due to their ability to accumulate lower concentrations in senescent leaves; preventing further contamination in surrounding ecosystems by encapsulating the pollutants instead of exporting them.